Multi-criteria decision-making model for optimal planning of on/off grid hybrid solar, wind, hydro, biomass clean electricity supply. (December 2021) - Ullah, Zia; Elkadeem, M.R.; Kotb, Kotb M.; Taha, Ibrahim B.M.; Wang, Shaorong
Abstract: Worldwide, the emerging trend of hybrid renewable energy sources integration in modern power systems is increasing due to privileged prices and clean electricity supply. However, the optimal planning of rural hybrid systems is a challenging and complex task, especially when different alternatives and sustainability aspects are considered. This paper develops an integrated decision-making approach for the optimal planning of a 100% renewable energy supply system comprising solar, wind, hydro, and biomass sources in a rural area located in Pakistan. An hourly-based design optimization analysis of twelve on/off-grid electrification alternatives is performed. The optimization model simultaneously addresses five sustainability criteria related to economy, reliability, ecology, society, and topography aspects. Furthermore, a novel hybrid decision-making model has developed to identify the unique best configuration with on-grid and off-grid options. The proposed model combines fuzzy analytic hierarchy process, multi-objective optimization based on ratio analysis technique for order of preference by similarity to an ideal solution, and evaluation based on distance from average solution methods. The results reveal that the solar-hydro-biomass battery with a life cycle cost of 10.9 M$ is the top-ranking off-grid system. When the hybrid system is connected to the grid, the solar-hydro-battery has found the most appropriate design with a life cycle cost of 12.96 M$. Both scenarios have a negligible capacity shortage of 0.09%. Ecologically, the optimal off-grid system produces only 408.37 kg/yr of CO2 due to the significant energy share of solar and hydro sources (99.3%). The optimal on-grid system produced the minimum CO2 with 29, 177.89 kg/yr compared to other alternatives. Also, employing the optimal on/off-grid designs require land area and jobs of 96.6 m 2, 14 jobs, and 118 m 2, 15 jobs, respectively. Overall, the developed approach with the presented case study offers a valuable benchmark and guidelines for investors and stakeholders to create realistic investment plans for the energy industry looking to push efficient inducements to encourage the high dissemination of renewables. Graphical abstract: Image 1 Highlights: 100% renewable energy system is established for on/off grid rural electrification. Twelve distinctive solar/wind/hydro/biomass-based hybrid energy alternatives are optimized. An integrated fuzzy-AHP/TOPSIS/EDAS/MOORA decision-making model is proposed. Cost, reliability, emission, social, and topographical criteria are simultaneously considered. Results prove the long-term sustainability of 100% renewable in rural Pakistan.